Pengaruh Servicescape dan Kualitas Komunikasi terhadap Loyalitas nasabah melalui Kepuasan nasabah sebagai variabel intervening (studi pada nasabah Bank Tabungan Pensiunan Nasional Kantor Cabang Yogyakarta) - Pricilia Sinta Sakinda; Henny Welsa; Muinah Fadhilah (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2020)
The purpose of this study was to examine direct and indirect effects of an integrated model of servicescape and communication quality upon customer loyalty, and considered customer satisfaction as intervening variable. This study used a causal design. The main data used in this study are primary data collected through the circulation of questionnaires to the respondents BTPN bank customers in Yogyakarta. The sampling technique using purposive sampling method to determine the sample based on the consideration of researchers. Data Analysis used Partial Least Square (PLS) yaitu SEM berbasis variance, dengan software SmartPLS. Based on the analysis it can be concluded that: the result of study supports the influence of servicescape to customer satisfaction, supports the influence of servicescape to customer loyalty, supports the influence of communication quality to customer satisfaction, supports the influence of communication quality to customer loyalty, supports the influence of customer satisfaction to customer loyalty, supports the influence of servicescape to customer loyalty through customer satisfaction, supports the influence of communication quality to customer loyalty through customer satisfaction.